Unveiling Non-Covalent Molecular Interactions: A Comprehensive Review Integrating DFT and Crystallographic Insights - W. O. N. Haryanti; I W. Sutapa; Sahidin; L. Ahmad; L. O. A. N. Ramadhan (International Journal of Acta Material, 2025)
Non-covalent interactions (NCIs) are crucial in elucidating molecular recognition, supramolecular architecture, and material properties. This review synthesizes findings from 20 recent studies (2013–2025), with a focus on key interaction types: hydrogen bonding, π–π stacking, Van der Waals forces, and less prevalent modes such as chalcogen bonding and excited-state interactions. Computational methodologies, particularly dispersion-corrected density functional theory (DFT), benchmark datasets (e.g., S22, HB300SPX), and emerging machine learning (ML) corrections, have markedly enhanced the accuracy of NCI modeling. Experimental techniques, including X-ray diffraction and infrared/Raman spectroscopy, continue to substantiate theoretical predictions. Hydrogen bonds are predominant in influencing structural stability and crystal packing, while π–π interactions play a vital role in stabilizing aromatic systems. Van der Waals interactions are particularly significant in layered materials and adsorption phenomena. Recent advancements, such as neural network potentials (NNPs) and non-empirical functionals (e.g., r²SCAN+MBD@HF), provide accurate predictions even in complex environments. This review underscores the interplay between theoretical and experimental approaches and highlights prospective directions in modeling weak interactions across a range of chemical systems.